Characterization of Silver Oxide Films Formed by Reactive RF Sputtering at Different Substrate Temperatures. (18th March 2014) - Reddy, P. Narayana; Reddy, M. Hari Prasad; Pierson, J. F.; Uthanna, S.
Abstract : Silver oxide (A2 O) films were deposited on glass and silicon substrates held at temperatures in the range 303–473 K by reactive RF magnetron sputtering of silver target. The films formed at room temperature were single phase Ag2 O with polycrystalline in nature, while those deposited at 373 K were improved in the crystallinity. The films deposited at 423 K were mixed phase of Ag2 O and Ag. Atomic force micrographs of the films formed at room temperature were of spherical shape grains with size of 85 nm, whereas those deposited at 473 K were with enhanced grain size of 215 nm with pyramidal shape. Electrical resistivity of the single phase films formed at room temperature was 5.2 × 10 −3  Ωcm and that of mixed phase was 4.2 × 10 −4  Ωcm. Optical band gap of single phase films increased from 2.05 to 2.13 eV with the increase of substrate temperature from 303 to 373 K, while in mixed phase films it was 1.92 eV.